Water Temple - Tadao Ando (Oz, 1994)
Hompukuji—a subordinate temple of Kyoto's Ninnaji, the head temple of Japan's Shingon sect—is located on the northeastern part of Awaji Island. This new main hall for Hompukuji is located at the rear of the temple grounds, on a hill that affords a sweeping view of Osaka Bay.